Effect of Modified Water Chestnut (Trapa bispinosa) Starch on Physical and Sensory Properties of Sponge Cakes: Effect of Water Chestnut Starch on Cakes - Lutfi, Zubala; Hasnain, Abid (Biological Sciences - PJSIR, 2009)
Study of the effect of chemically and physically modified water chestnut (Trapa bispinosa) starch on volume index, symmetry index and uniformity index of sponge cake revealed that addition of acetylated starch (3%) increased the volume index of control sponge cake to a greater extent. In case of acid-thinned starch, increase in symmetry index was not very significant except that of concentration of 1%. At 4% - 5% concentration, pregelatinized starch and acid-thinned starch showed excellent uniformity index. Acetylated starch at 1% and 5% concentration significantly increased the grain structure.